The Relationship Between Dimensions of the Family Quality Index Provincial Level Throughout Indonesia in 2021 - Puspitawati, Herien; Sarma, Ma'mun; Sutarman, Deddy Cahyadi; Septiana, Maya; Cahayani, Octaria Intan (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The Family Quality Index (IKK) measures the success of family development in Indonesia, and can be used as a basis for planning and indicators of successful family development at the central, provincial/regional, and regency/city levels. The objectives of the study were to analyze (1) the Cronbach’s alpha reliability test and the content validity of IKK indicators, (2) the achievements of IKK at the provincial and national levels, and (3) the relationship between indicators and dimensions of IKK. The research method is a quantitative analysis of BPS secondary data for 2021. Cronbach’s alpha was 0.50, and content validity was between 0.03 and 0.77. The provincial IKK score in 2021 range from 65.16 to 76.80, with a national achievement score of 73.43. Three provinces were included in category 3, namely